Analisis Yuridis Tanggung Jawab Pelaku Usaha Terhadap Konsumen Akibat Keterlambatan Penerbangan - Dedy Fahrizal; Darwis Anatami; Siti Nurkhotijah (Penerbit Goodwood, 2022)
Law Number 1 of 2009 concerning Aviation and Regulation of the Minister of Transportation Number 89 of 2015 concerning Handling of Flight Delays (Delay Management) in Scheduled Commercial Air Transport Business Entities in Indonesia which specifically regulates flight delays. However, sometimes flight officers sometimes do not provide compensation or compensation for the delay (delay) to passengers in accordance with applicable rules as a form of legal protection. Purpose: The purpose of writing this journal is to find out the legal arrangements for the responsibility of business actors to consumers due to flight delays, implementation, obstacle factors and efforts to implement business actors' responsibilities to consumers due to flight delays. Methodology: The research that is used in writing this thesis is normative juridical research. Results: The results of the study show that the legal arrangements for the responsibility of business actors to consumers due to flight delays are regulated in Law Number 8 of 1999 concerning Consumer Protection and Law Number 1 of 2009 concerning Aviation along with the Regulation of the Minister of Transportation Number 89 of 2015 concerning Handling of Flight Delays. (Delay Management) in Scheduled Commercial Air Transport Business Entities in Indonesia. The implementation of the responsibility of business actors to consumers due to flight delays does not run optimally, where there are still some weaknesses in the elements of the legal structure, legal substance and legal culture, the constraint factors faced are the legal structure factors related to the non-optimal performance of institutions authorized to fulfill aviation consumer rights, legal substance factors that do not stipulate strict sanctions for aviation business entities that do not pay compensation due to delays, and legal cultural factors the consumer's own level of legal awareness is low on the rights that can be obtained in the event of flight delays. . Efforts to overcome these obstacles are legal remedies by optimizing the performance of related institutions, legal remedies that can be taken by airplane passengers, and legal efforts for airplane passengers through the Non-Governmental Consumer Protection Agency (LPKSM).